Thermo-kinetic analysis, thermodynamic parameters and comprehensive pyrolysis index of Melia azedarach sawdust as a genesis of bioenergy - Agnihotri N.; Gupta G.K.; Mondal M.K. (My University, 2025)
Energy demands are dynamic and intensifying demand of energy led to execute this study in order to analyze the thermal degradation characteristics of Melia azedarach sawdust (MAS) collected from sawmill intending to examine its pyrolytic performance for biofuel production. The inceptive characterizations which include proximate, ultimate, component analysis and higher heating value (HHV) were carried out so as to scrutinize its worth for pyrolysis. Furthermore, thermogravimetric (TG) experiments were performed in temperature hovering from ambient to 900 ℃ at three different slow rates of heating (10, 20 and 30 ℃ min−1) under inert condition. Findings of TG analysis revealed 210 to 480 ℃ as the maximum devolatilization temperature range during thermal degradation of MAS. Kinetic and thermodynamic parameters were estimated using three iso-conversional models, i.e. Kissinger–Akahira–Sunose (KAS), Flynn–Wall–Ozawa (FWO) and Starink and average activation energy was found to be 161.18, 162.68 and 161.41 kJ mol−1, respectively. The obtained values of Gibbs free energy (ΔG) were 185.98, 185.91 and 185.97 kJ mol−1 and that of change in enthalpy (ΔH) were 155.91, 157.47 and 156.19 kJ mol−1 for KAS, FWO and Starink models, respectively. Master plot along with Criado method revealed a complex mechanism of the reaction. Average and maximum decomposition rates, as well as initial devolatilization and peak temperatures, shifted to higher values with an increase in heating rate. Comprehensive pyrolysis index (CPI) exhibited higher value at higher heating rate which indicates the suitability of pyrolysis of MAS at a high heating rate. All these findings coupled with 15.43 MJ kg−1 HHV inferred the suitability of MAS for pyrolysis as it exhibits remarkably high potential for biofuel generation. Thus, it can be a concrete step towards clean energy generation along with a balance between economy and ecology with desire to strengthen our energy self-sufficiency. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.